Correction to: A preliminary study of cell-based bone tissue engineering into 3D-printed β-tricalcium phosphate scaffolds and polydioxanone membranes (Scientific Reports, (2024), 14, 1, (31184), 10.1038/s41598-024-82334-6) - Pitol-Palin, L. [UNESP]; Moura, J. [UNESP]; Frigério, P. B. [UNESP]; de Souza Batista, F. R. [UNESP]; Saska, S.; Oliveira, L. J.M.; Matsubara, E. Y.; Pilatti, L.; Câmara, D.; Lizier, N.; Blay, A.; Shibli, J. A.; et al. (Springer Nature, 2025)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-82334-6, published online 28 December 2024 The original version of this Article contained an error in Affiliation 3, which was incorrectly given as ‘Pesquisa e Desenvolvimento Ltda, 2721Av. Indianápolis, São Paulo 04063-005, Brazil.’ The correct affiliation is listed below: Nicell Pesquisa e Desenvolvimento Científico Ltda., 2721, Indianópolis, São Paulo, 04063-005, Brazil. The original Article has been corrected.